2021
DOI: 10.3390/atoms9040101
|View full text |Cite
|
Sign up to set email alerts
|

On the Feasibility of Rovibrational Laser Cooling of Radioactive RaF+ and RaH+ Cations

Abstract: Polar radioactive molecules have been suggested to be exceptionally sensitive systems in the search for signatures of symmetry-violating effects in their structure. Radium monofluoride (RaF) possesses an especially attractive electronic structure for such searches, as the diagonality of its Franck-Condon matrix enables the implementation of direct laser cooling for precision experiments. To maximize the sensitivity of experiments with short-lived RaF isotopologues, the molecular beam needs to be cooled to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…21 Computational studies have shown that because of high electronic transition energies RaF + and RaH + cations are not well suited for laser manipulations. 22 Favorable vibrational branching ratios were reported for a transition of TlF + lying in the UV region. 23 In the context of precision measurements, highly charged heavy cations offer additional benefits.…”
Section: Introductionmentioning
confidence: 99%
“…21 Computational studies have shown that because of high electronic transition energies RaF + and RaH + cations are not well suited for laser manipulations. 22 Favorable vibrational branching ratios were reported for a transition of TlF + lying in the UV region. 23 In the context of precision measurements, highly charged heavy cations offer additional benefits.…”
Section: Introductionmentioning
confidence: 99%